2021
DOI: 10.1108/k-12-2020-0865
|View full text |Cite
|
Sign up to set email alerts
|

Applying machine learning approach to predict students’ performance in higher educational institutions

Abstract: Purpose Academic success and failure are relevant lifelines for economic success in the knowledge-based economy. The purpose of this paper is to predict the propensity of students’ academic performance using early detection indicators (i.e. age, gender, high school exam scores, region, CGPA) to allow for timely and efficient remediation. Design/methodology/approach A machine learning approach was used to develop a model based on secondary data obtained from students’ information system in a Nigerian universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 54 publications
0
27
0
2
Order By: Relevance
“…The second highest is IBM SPSS for statistical approaches with 13% ( [13], [66], [70], [82]- [84], [86], [95], [120], [136]). Other most-used tools include Microsoft Excel (17%) ([20], [52], [117], [123], [135], [71], [82]- [84], [86], [89], [112], [115]), RapidMiner Studio (9%) ( [13], [49], [70], [86], [91], [107], [131]), Jupyter Notebook (7%) ( [115], [123], [124], [127], [132]), Orange and R Studio (4%) ( [62], [87], [116], [125], [128], [133] respectively), and Tableau (3%) ( [77], [127]).…”
Section: Prediction Approaches Algorithms Learning Outcome Type and T...mentioning
confidence: 99%
“…The second highest is IBM SPSS for statistical approaches with 13% ( [13], [66], [70], [82]- [84], [86], [95], [120], [136]). Other most-used tools include Microsoft Excel (17%) ([20], [52], [117], [123], [135], [71], [82]- [84], [86], [89], [112], [115]), RapidMiner Studio (9%) ( [13], [49], [70], [86], [91], [107], [131]), Jupyter Notebook (7%) ( [115], [123], [124], [127], [132]), Orange and R Studio (4%) ( [62], [87], [116], [125], [128], [133] respectively), and Tableau (3%) ( [77], [127]).…”
Section: Prediction Approaches Algorithms Learning Outcome Type and T...mentioning
confidence: 99%
“…Using machine-learning to predict academic success of students at the American University of Nigeria, Yakubu and Abubakar [ 28 ] found that females were 1.2 times more likely to succeed academically than males and that juniors and seniors were more likely to achieve higher cumulative GPA. Kalman et al [ 29 ] studied students’ perspectives of online learning in upper-level and lower-level chemistry courses at a four-year undergraduate university in Georgia during the Spring 2020 transition to online learning.…”
Section: Related Literaturementioning
confidence: 99%
“…Machine learning algorithms in [20,21] and data mining techniques in [22,23] are considered as one overview of student performance prediction modeling for further education in both pairs of these papers. Application of machine learning in predicting performance for computer engineering students is subject of the manuscripts [24,25] and data mining techniques are applied in predicting further education for students that study medical curriculum [26].…”
Section: Related Studiesmentioning
confidence: 99%